The cohort size-wage relationship in Europe - Duncan Roth; John Moffat (European Regional Science Association (ERSA), 2013)
The demographic and education composition of European countries is changing: the population share of young individuals is declining while that of the highly educated is rising. This study estimates the impact of cohort size on wages using data on several European countries to cast light on the economic consequences of these changes in the profile of the labour force. Theory predicts that within each educational class, similarly aged individuals compete for jobs but are only imperfectly substitutable with workers of different ages. Consequently, an increase in the population share of a specific age-education group is expected to have a depressing effect on the real wage rate of that group. To test this prediction empirically, this paper uses the 2010 release of the longitudinal EU-SILC which is a comprehensive data set covering individual and household-level microdata for a period of 4 years and 24 European countries. This paper differs from the preceding literature by analysing the effect of cohort size on individual wages rather than on the average wage of a specific age-education group which allows controlling for potentially confounding effects at the individual level. The effect of cohort size on male wages is identified through instrumental variables (IV) estimation that uses the birth rate at an individual?s year of birth as an instrument for the potentially endogenous cohort size variable. In contrast to other identification strategies, this instrument is able to account for endogeneity caused by individual self-selection into specific educational groups as well as into specific geographical areas. The results support the hypothesis that cohort size has a negative effect on male wages, particularly for the highly educated. However, these negative cohort size effects are not persistent.
Keywords: J10; J21; J31; 330; Cohort size; wages; causal effect; NUTS 1